ANALISIS PROGRAM PENGAJARAN REMEDIAL DALAM MENCAPAI KRITERIA KETUNTASAN MINIMAL (KKM) MATA PELAJARAN PERBANKAN DASAR KELAS X - Paskia Wulandari; Mashudi Mashudi; F. Y. Khosmas (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research is to find out how remedial teaching using discussion and question and answer methods can help students to achieve the Minimum Completeness Criteria (KKM) for Basic Banking Subjects. The type of research used is qualitative research with case study method. The data sources of this study were students of class X AKL I and X AKL II who took part in remedial activities and a list of grades from students of class X AKL I and X AKL II. The data collection instruments started from observation, interviews, and documentation studies. The data analysis technique includes 3 activities, namely data reduction/data reduction, data presentation/data display, and conclusion drawing/conclusion drawing.From the results of the analysis carried out in this study, it can be concluded that remedial teaching using discussion and question and answer methods can help students in class X AKL I and X AKL II achieve the Minimum Completeness Criteria (KKM) for Basic Banking Subjects. The advice given in maximizing remedial teaching in achieving the Minimum Completeness Criteria (KKM) so that it is more ef ective and ef icient is to pay more attention to the time to carry out remedial teaching, because the discussion and question and answer process requires a lot of time and each student has questions or answers. dif erent opinion.Keyword: Remedial Teaching, Minimum Completeness Criteria (KKM) and Students.